Subjective Life Expectancies, Time Preference Heterogeneity, and Wealth Inequality - Richard Foltyn; Jonna Olsson (ZBW - Leibniz Information Centre for Economics, 2024)
This paper examines how objective and subjective heterogeneity in life expectancy affects savings behavior of healthy and unhealthy people. Using data from the Health and Retirement Study, we first document systematic biases in survival beliefs across self-reported health: those in poor health not only have a shorter actual lifespan but also underestimate their remaining life time. To gauge the effect on savings behavior and wealth accumulation, we use an overlapping-generations model where survival probabilities and beliefs evolve according to a health and survival process estimated from data. We conclude that differences in life expectancy are important to understand savings behavior, and that the belief biases, especially among the unhealthy, can explain up to a fifth of the observed health-wealth gap.
Keywords: D15; E21; G41; I14; 330; life expectancy; preference heterogeneity; subjective beliefs; life cycle